عين؛ أشعار الإيمان = 'Ayn: poems of faith ('Ayn: ash'ar al-Iman) - Abd. Rahman, Akmal Khuzairy; Yaakub (trans.), Muhamadul Bakir; Dollah (trans.), Nafi@Hanafi (Institut Terjemahan & Buku Malaysia, 2014)
Kemala's poetry draws upon the long traditions of Malay poetry, the majesty of the Qur'an and the themes of Sufi thought. The exploration of meaning and mysticism is the core of Kemala's work, the theme for which poetry and poetry alone is suited. -Merryl Wyn Devies, Inquiry, September 1987.